Implementation of the Chalk and Talk Strategy to Improve Mathematics Learning Outcomes for Students in Class VII.2 SMP Muhammadiyah Parepare - Sumi, Sumi; Nurdin, Nurdin; Anugrah, Dian (Sublim: Jurnal Pendidikan, 2023)
This study aims to find out that mathematics learning outcomes can be improved through the Chalk and Talk learning strategy in class VII.2 students of SMP Muhammadiyah Parepare. This type of research is classroom action research whose implementation includes: planning (plaining), implementing actions, observing or observing, and reflecting. The subjects of this study were students of class VII.2 even semester of SMP Muhammadiyah Parepare in the academic year 2014/2015 with a total of 26 students, consisting of 14 male students and 12 female students. This research was carried out in two cycles, each meeting three times the learning process and one meeting a learning outcome test was conducted. The data collection technique used in this research is data about students' mathematics learning outcomes obtained using the test technique given at the end of each cycle, while data about student activities and teacher activities are taken using observation sheets when the learning process takes place in the classroom. class.Based on the results of research and discussion during two cycles, it can be concluded that the mathematics learning outcomes of students in class VII.2 SMP Muhammadiyah Parepare have increased from cycle I to cycle II after the implementation of the Chalk and Talk learning strategy . It is characterized by: (a) increasing the average mathematics learning outcomes for students in the first cycle is 42.88 % to 83.88 % in the second cycle. (b) increasing the percentage of students ' mathematics learning completeness , which is 26.9 % in cycle I to 92.3 % in cycle II or classically completed . (c) an increase in the average activity of students in participating in learning in cycle II. And (d) the increase in the average ability of teachers in managing learning from cycle I to cycle II.